Party Newspapers Perspectives and Choices - Espírito Santo, Paula do (2021)
The focus of this article is on how different parties use its party newspapers as instruments of political communication, in the current political context, particularly in Portuguese press. As is to be expected, the newspapers reproduce the party’s vision and help disseminate their leaders’ political ideals and proposals. There are, however, significant differences in the history and format of each publication, in terms of the way the political message is put across and the scope of the subjects addressed. This article is based on a content analysis technique, through a categorical qualitative and quantitative systematization. The expected results are centered on the discussion about the communication strategies of ideologically different party newspapers which are visible in front pages. Moreover, this study is expected to contribute to the discussion about personalization in politics, focusing and considering in particular party newspapers. This is a subject that has been scarcely investigated in communication studies and in political science, despite the presence and ideological place of party newspapers in the past and at present. The aim of this article is to make a contribution toward demonstrating and boosting the interest of this important support to party life and politics.